The Concept of Islamic Inclusive Education in Early Childhood (Critical Analysis of STEAM Learning Model) - Hasanah, Hasanah; Suyadi, Suyadi; Lessy, Zulkipli (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This research aims to investigate the concept of inclusive based on Islamic education by examining the learning model of STEAM (Science, Technology, Engineering, Art, and Mathematics) in PAUD critically and exploring how the development of religious aspects in the STEAM model can improve the holistic education of early childhood. The research method used by the authors is qualitative with library research, and the data collection used is documentation by searching for data from books, journals, and other sources related to the research problem and analysis techniques using content analysis. The research results generally emphasize that inclusive education in the STEAM context must integrate aspects of spirituality with science. Inclusive education based on multipotential and multidimensional is important in forming individuals who are tough and competitive in facing the challenges of the digital age. This aligns with the understanding that humans have multidimensionality, which needs to be developed comprehensively from an early age. Islamic inclusive education is by the Islamic view of human nature, where humans are created with various natures. In Islam, the term